Manfaat Penggunaan Iklan pada Media Sosial dan Google oleh UMKM (Usaha Mikro, Kecil dan Menengah) - Dyanti, Debora Molina; Widiale, Vannessa Putri (Universitas Batanghari Jambi, 2024)
Information technology is increasingly developing and provides various benefits for its users, so that it becomes part of carrying out daily activities. In line with technological developments, UMKM should adapt to the era of digitalization. However, not all UMKM are ready to adapt. Many UMKM do not have the knowledge and skills regarding digital marketing, especially social media and google. This research was conducted using qualitative methods using primary and secondary data with the research object being UMKM which are under the guidance of JakPrenuer. It is hoped that this research can help UMKM to find out the benefits of using advertising on social media and google so that UMKM can have the knowledge to be part of digitalization.